The place of children’s literature in the literary system - Mínguez-López, Xavier (Íkala, Revista de Lenguaje y Cultura, 2015)
The status of children’s literature within the literary system has generated all kind of discussions. We can find those who considered there was no such a thing, and it should rather be integrated to literature in general. On the oppositeside, there were those who called for its own space even from a critical point of view. In this debate it is necessary to resort to wider theories in order to realize which relationship children’s literature has to the general literary system. Undoubtedly, the theories that better help define such a relationship are Pierre Bourdieu’s theory of literary field, and Itamar Even-Zohar’s theory of polysystems. Although generally named in children’s literature studies to legitimize their change of status from the 1970’s, they are usually not developed from this paradigm. The author’s intention is to see how these theories helpbetter understand the phenomenon of children’s literature and its relation to general literature. From this point of view, the most important contributions are the removal of formal patterns in the definition and introduction of social parameters, such as production, reception, consumption, etc., which definitely influence its configuration.